Quality Control of Raw Materials on Red Snapper (Lutjanus sp.) Freezing Process in PT. Tridaya Jaya Manunggal Pasuruan East Java - Winona Valeria Siregar; M. Nur Ghoyatul Amin (Universitas Airlangga, 2021)
Red snappers are fishery commodities which have high market values. Raw materials of red snappers are important elements which determine the quality of the final products. Therefore, an enhancement of raw materials quality should be conducted through quality supervision and examination when the raw materials are retrieved, stored, and about to enter production process. The aim of this fieldwork practice is to find out the raw materials quality control on red snapper freezing process in PT. Tridaya Jaya Manunggal Pasuruan, East Java. The data taken consists of primary and secondary data which are processed descriptively. Data collection techniques through observation, interviews, active participation and literature review. PT. Tridaya Jaya Manunggal has implemented quality control on production process, starting from raw materials retrieval until these raw materials become final products. The quality control of raw red snappers were done in accordance with the quality control procedures which are plan, do, check, and action. The results of implementing quality control which were executed with organoleptic examination, temperature, Total Volatile Base (TVB), microbiology, and heavy metals on raw red snappers. Raw materials which didn’t meet the required standard were rejected, and then they were processed to be second grade products.